2008
DOI: 10.1002/psc.988
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pH effects on biophysical and morphological properties of self‐assembling peptide RADA16‐I

Abstract: It has been found that the self-assembling peptide RADA 16-I forms a beta-sheet structure and self-assembles into nanofibers and scaffolds in favor of cell growth, hemostasis and tissue-injury repair. But its biophysical and morphological properties, especially for its beta-sheet and self-assembling properties in heat- and pH-denatured conditions, remain largely unclear. In order to better understand and design nanobiomaterials, we studied the self-assembly behaviors of RADA16-I using CD and atomic force micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 42 publications
7
98
0
Order By: Relevance
“…When heated to 90°C, the self-assembled structure of R4 changes into aggregates ( Figure 5F). Previous study 31 has shown that RADA16-I exhibits β-sheet structure and forms unordered aggregates at 70°C, indicating that the nanostructure of R4 is more stable than that of RADA16-I.…”
Section: Stability Of Self-assembling Peptides R3 and R4mentioning
confidence: 85%
“…When heated to 90°C, the self-assembled structure of R4 changes into aggregates ( Figure 5F). Previous study 31 has shown that RADA16-I exhibits β-sheet structure and forms unordered aggregates at 70°C, indicating that the nanostructure of R4 is more stable than that of RADA16-I.…”
Section: Stability Of Self-assembling Peptides R3 and R4mentioning
confidence: 85%
“…According to the study by Z. Ye and X. Zhao et al, the random coils and β-turn of (RADA) 4 via hydrogen or ionic bonds would directly affect the stability of the β-sheet and nanofibers. 40 Thus, it is necessary to compare the β-sheet content with the random coils and β-turn. On the basis of this, the β/TR ratios have been calculated and compared, which supported that 25% v/v nanoparticle solution in hydrogel did not drastically affect the assembly of (RADA) 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The chitosan nanoparticles were hard to distinguish from fiber A typical CD spectrum of (RADA) 4 β-sheet structure contains a minimum at ∼216 nm (β-sheet contents) and a maximum at 196 nm (the degree of β-sheet twist). 40 The nanoparticle solutions do not have absorption in CD examination, see Figure S2.…”
Section: Nanoparticle Characterization: Effect Of Phmentioning
confidence: 99%
“…From the circular dichroism analysis, the RADA16 peptide had a typical β-sheet structure (minimum molar ellipticity at 215-217 nm and maximum at 195-206 nm), with 50.6% β-sheet content ( Figure 3 and Table 1, S (r) + S [d]) according to the CDPro software analysis. 19 However, when RADA16 was stirred with PTX for 48 hours, there was an approximately 18.4% decrease in the β-sheet content and a 19.8% increase in the unordered structure content. Dynamic light scattering measurements showed that the diameter of nanofibers from a pure RADA16 solution was in the range of 10-50 nm.…”
Section: Interaction Of Rada16 and Ptxmentioning
confidence: 96%